How an Advertising Disclosure Alerts Young Adolescents to Sponsored Vlogs: The Moderating Role of a Peer-Based Advertising Literacy Intervention through an Informational Vlog - De Jans, Steffi; Cauberghe, Veroline; Hudders, Liselot (Journal of advertising, 2018)
Sponsored vlogs (video blogs that embed advertising) are increasingly targeting young adolescents and challenging their abilities to critically process advertising. This study examined the impact of an advertising disclosure on young adolescents' advertising literacy (i.e., advertising recognition and affective advertising literacy) for sponsored vlogs. In addition, the underlying mechanisms, including advertising literacy and influencer effects (i.e., influencer trustworthiness and parasocial interaction [PSI]), that can explain the influence on advertising effects (i.e., purchase intention) were examined. Finally, the moderating impact of a peer-based advertising literacy intervention was investigated through an informational vlog about advertising. The results of a 2 × 2 between-subjects experimental study (advertising disclosure: no disclosure versus disclosure; peer-based advertising literacy intervention: regular versus informational vlog) with 160 young adolescents (ages 11 to 14) showed that an advertising disclosure increased young adolescents' recognition of advertising and their affective advertising literacy for sponsored vlogs, and that only affective advertising literacy negatively affected influencer effects (influencer trustworthiness and PSI) and subsequently purchase intention. Regarding the moderating role of this peer-based advertising literacy intervention, this study showed that an advertising disclosure can also have positive effects on the influencer and subsequently on advertising effects when young adolescents are informed about advertising through an informational vlog.